2021
DOI: 10.1186/s43019-021-00087-2
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-assisted vs conventional surgery in medial unicompartmental knee arthroplasty: a clinical and radiological study

Abstract: Background The use of unicompartmental knee arthroplasty (UKA) has increased and new technologies have been developed to improve patient survival and satisfaction, soft tissue balance, alignment, and component size. Robot-assisted systems offer an increase in surgical precision and accuracy. The purpose of this study is to evaluate the precision of component position using five radiological parameters in conventional and robotic-assisted medial UKA using the NAVIO system. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
0
11
1
3
Order By: Relevance
“…This demonstrates the accuracy of bone and implant positioning in RUKA with the Mako system. Although the results are not identical to those of other studies, they are similar in that RUKA increased the accuracy of implant positioning [ 5 , 13 , 14 , 15 , 16 ]. A study by Bell et al [ 5 ] demonstrated that the implantation of components within 2° of the target position, when using the Mako system, was achieved in a relatively large proportion of patients.…”
Section: Discussioncontrasting
confidence: 62%
“…This demonstrates the accuracy of bone and implant positioning in RUKA with the Mako system. Although the results are not identical to those of other studies, they are similar in that RUKA increased the accuracy of implant positioning [ 5 , 13 , 14 , 15 , 16 ]. A study by Bell et al [ 5 ] demonstrated that the implantation of components within 2° of the target position, when using the Mako system, was achieved in a relatively large proportion of patients.…”
Section: Discussioncontrasting
confidence: 62%
“…Then, several studies have shown a decrease in postoperative pain with the use of the robot [ 20 , 21 ]. This may also explain the decrease in the rate of stiffness in patients operated with robotic.…”
Section: Discussionmentioning
confidence: 99%
“…With improved accuracy in regard to restoration of joint line and balanced flexion and extension gaps, theoretically surgeons can decrease their rates of failure [ 21 ]. UKA has been showed to have better success rates at midterm follow-up when robotic-armed assistance was used [ [22] , [23] , [24] ]. In total hips, the computer-based software allows the surgeon to individualize the cup inclination/version, thereby decreasing dislocation rates [ 25 ].…”
Section: Discussionmentioning
confidence: 99%